2023
DOI: 10.3390/su15129597
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Disequilibrium and Dynamic Evolution of Eco-Efficiency in China’s Tea Industry

Abstract: Eco-efficiency is a significant target for evaluating the agricultural ecosystem and measuring sustainable agricultural development through quantitative analysis. It is also an essential part of constructing the ecological tea garden, which offers a directional function in realizing the green development of the tea industry. After measuring the eco-efficiency of China’s tea industry using the super-efficiency SBM model, this paper analyzes the spatial disequilibrium and dynamic evolution trend of the eco-effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…They found that economic factors, environmental governance, and technological progress were major determinants affecting ecological efficiency. Zhang, H. (2022) [24], Jiang, W. (2023) [25], and others, based on the Malmquist ecological efficiency index, studied the spatial-temporal evolution characteristics of interprovincial ecological efficiency in China. They discovered that the ecological efficiency in eastern regions was generally higher than in western regions and exhibited an overall upward trend over the years.…”
Section: ) Research On Interprovincial Ecological Efficiency In Chinamentioning
confidence: 99%
“…They found that economic factors, environmental governance, and technological progress were major determinants affecting ecological efficiency. Zhang, H. (2022) [24], Jiang, W. (2023) [25], and others, based on the Malmquist ecological efficiency index, studied the spatial-temporal evolution characteristics of interprovincial ecological efficiency in China. They discovered that the ecological efficiency in eastern regions was generally higher than in western regions and exhibited an overall upward trend over the years.…”
Section: ) Research On Interprovincial Ecological Efficiency In Chinamentioning
confidence: 99%
“…China is one of the six major tea producing countries in the world, accounting for approximately 42% of the global production. According to research reports from some relevant institutions, the production of tea reached 2.97 million tons in 2020 (Jiang et al, 2023;Shu et al, 2023;Zhang et al, 2023). However, freshly harvested tea has high moisture content and needs to be dried and dehydrated through the drying process to reduce the moisture content below 5%.…”
Section: Introductionmentioning
confidence: 99%